JENIS-JENIS KEWIRAUSAHAAN YANG MEMPENGARUHI TINGKAT KEPRIBADIAN DAN KETERAMPILAN INTERPERSONAL TERHADAP KEBERHASILAN WIRAUSAHA - Lediana Lediana; Nofikasyara Dhea; Fortunata Blandina Panamuan (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This article intends to find out the level of personality and interpersonal skills of an entrepreneur towards the types of entrepreneurship that are built. By applying research methods, namely literature studies, where the author does not need to go directly into the field. In this method, the author seeks to collect, evaluate and synthesize various literature sources relevant to the topic discussed. Evident from several sources, the author found that entrepreneurship is not only about building a business, but entrepreneurship can have a significant effect on personality levels and interpersonal skills, which are the key to success and building sustainable relationships with others. There are six types of entrepreneurship that the author includes in this article, namely, trade entrepreneurship, services, the world of teaching and learning, the world of culture and art, agriculture and industry. Various types of personalities are formed from the six types of entrepreneurship displayed by the author, depending on the experience and challenges experienced by entrepreneurs in running their businesses. The average personality formed from entrepreneurship is creative, innovative, independent, and diligent. Not to forget communication skills, leadership and responsibility are also built when building a business.